Jinx and the Doom fight crime! - Mantchev, Lisa (Simon & Schuster Books for Young Readers, 2018)
Instead of fighting each other, Jinx and her little brother The Doom spend their days fighting crime, protecting the planet, defending the innocent, and taking lunch breaks.